2010
DOI: 10.1038/nnano.2010.45
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of thin C60 films by metal nanoparticles

Abstract: Metal nanoparticles supported by thin films are important in the fields of molecular electronics, biotechnology and catalysis, among others. Penetration of these nanoparticles through their supporting films can be undesirable in some circumstances but desirable in others, and is often considered to be a diffusive process. Here, we demonstrate a mechanism for the penetration of thin films and other nanoscopic barriers that is different from simple diffusion. Silver clusters that are soft-landed onto a monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…Revealing the structural dynamics of a cluster on a surface is crucial to understanding catalytic systems. Another example employs STM to investigate the diffusivity of Au clusters deposited on monolayers of C 60 supported by an Au(111) under-layer 80 .…”
Section: Preparation and Characterization Of Small Clustersmentioning
confidence: 99%
“…Revealing the structural dynamics of a cluster on a surface is crucial to understanding catalytic systems. Another example employs STM to investigate the diffusivity of Au clusters deposited on monolayers of C 60 supported by an Au(111) under-layer 80 .…”
Section: Preparation and Characterization Of Small Clustersmentioning
confidence: 99%
“…This step ensures that the clusters do not undergo fragmentation upon landing. 27,28 The substrates were prepared by atomic layer deposition (ALD) of alumina on top of a native oxide of a silicon wafer (SiO 2 /n-type, phosphorusdoped Si (100)), yielding an ∼3 monolayer (ML) thin hydroxylated amorphous alumina film. The clusters of a single size were deposited on the substrate at a surface coverage of 5% of a ML, containing a total of 1.11 × 10 13 Cu 4 clusters on the sample surface, at an estimated average cluster-to-cluster distance of 3 nm.…”
mentioning
confidence: 99%
“…Most of the clusters have a height of 1.4 nm, while a few are bigger, probably due to coalescence, because the coverage is already too large in this area. Even though this height is slightly larger than the height measured for Ag 55 clusters on top of a C 60 film 29, we expect that the clusters penetrate the Xe film. We observed that for clusters produced by buffer layer assisted growth on Xe films a film thickness larger than 10 ML is needed to separate the clusters from the substrate, and different to the quite stable STM image in Fig.…”
Section: Resultsmentioning
confidence: 55%